Proceedings of Fifth International Conference on Soft Computing for Problem Solving SocProS 2015, Volume 2 - Pant, Millie; Deep, Kusum; Bansal, Jagdish Chand; Nagar, Atulya; Das, Kedar Nath.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This two volume book is based on the research papers presented at the 5th International Conference on Soft Computing for Problem Solving (SocProS 2015) and covers a variety of topics, including mathematical modelling, image processing, optimization methods, swarm intelligence, evolutionary algorithms, fuzzy logic, neural networks, forecasting, medical and health care, data mining, etc. Mainly the emphasis is on Soft Computing and its applications in diverse areas. The prime objective of this book is to familiarize the reader with the latest scientific developments in various fields of Science, Engineering and Technology and is directed to the researchers and scientists engaged in various real-world applications of 'Soft Computing'.
Fuzzy Bi-Criteria Optimization Model for Fault-tolerant Distributed Embedded Systems under Reuse-or-Build-or-Buy Strategy Incorporating Recovery Block Scheme -- Chapter 86. Hybrid Multi-criteria Decision Making Approach for Supplier Evaluation in Fuzzy Environment -- Chapter 87. Mathematical Modeling of Multistage Evaporator System in Kraft Recovery Process.
Keywords: Computational intelligence; Signal processing; Artificial intelligence; Computational Intelligence; Signal, Speech and Image Processing; Artificial Intelligence